TWO NEW AEGORHINUS SPECIES (COLEOPTERA: CURCULIONIDAE: ATERPINAE) FROM CHILE (Acta Entomológica Chilena, 2022)
Two new Aegorhinus species are described: A. maulinus n. sp. and A. bilinealus n.sp. Based onmorphological features the former is associated to A. servillei and the latter to A. albolineatus - A. superciliosusspecies group. Adults and some other illustrations of internal and external structures are given as complemenlfor recognition. Geographical distribution of A. delfini (Germain), an endemic component of the Magellanicforest, is precised.